Patents in the pharmaceutical industry: between ethics and property rights (2003)
The article presents a reflection on one of the greater challenges which the contemporary State is confronted with, related to guaranteeing the effective application of the fundamental rights, besides having to solve the conflicts that arise due to the rivalry between either fundamental rights or between some of these and others known as second or third generation rights. The conflict between the protection to the intellectual property rights, as in the case of the patents of the pharmaceutical multinationals, and the fundamental right to life is considered. It is observed that the interests of these companies have prevailed, as if the fundamental value to protect was the profit of these multinationals, or their efficiency, and not the right to health of the individuals which bears a direct relation with the right to the life. This situation is aggravated still more when the State, instead of being on the side of the weaker and offering him protection, safeguards the stronger who abuse of their dominant position, exerting the monopoly on the  production of many essential medicines.